IoT in Smart Gym Equipment: Revolutionizing Fitness through Connected Technology - Garvit Chandna, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Internet of Things (IoT) technology in fitness equipment marks a transformative era in the exercise industry, revolutionizing how individuals engage with their workout routines. This technological advancement encompasses sophisticated sensor networks, predictive maintenance systems, and real-time performance monitoring capabilities that enhance both user experience and facility operations. Smart gym equipment now incorporates advanced biomechanical analysis, automated safety protocols, and personalized risk assessment features, enabling precise movement tracking and injury prevention. The implementation of live metrics and community engagement features through leaderboard systems and interactive streaming has fostered increased motivation and adherence to fitness goals. The convergence of artificial intelligence, virtual reality, and blockchain technology is shaping the future of fitness, offering unprecedented levels of personalization and data security. These innovations have collectively transformed traditional workout sessions into data-driven, connected experiences that optimize performance, ensure safety, and maintain user engagement while streamlining facility management and equipment maintenance.
Keywords: IoT fitness technology; smart gym equipment; connected workout systems; exercise performance monitoring; fitness data analytics